Making mathematics meaningful for culturally and linguistically diverse students with a mathematics learning disability: a focus on culturally responsive practices - Tran, Le M.; Castro Schepers, Ofelia (Frontiers in Education, 2023)
Elements of the Individualized Education Programs (IEP) for culturally and linguistically diverse students with mathematics learning disabilities (CLD-MD) have long been inadequate at capturing the cultural, linguistic, and learning needs of this subset of students. Efforts to address the knowledge gap of understanding of culturally and linguistically diverse (CLD) students within the mathematics community, specifically those focused on mathematics learning disabilities, have typically focused on strategies for specific mathematics concepts and skills such as computation, word-problem solving, or fraction strategies. As the population of CLD students who are identified both as culturally and linguistically diverse and having a specific learning disability in the area of mathematics increases, there have been increased efforts to identify strategies that support the complexity that their identities bring to mathematics instruction. Much of this work is nascent in the field, and as such, this paper provides a variety of evidence-based strategies that provide appropriate whole-class instruction and intensive interventions for CLD-MD students.